Pengaruh Rendaman Air Gambut terhadap Durabilitas AC-WC - Harahap, Amal Risky; Wiyono, Sugeng; Elizar, Elizar; Puri, Anas (Department of Civil Engineering, Diponegoro University, 2022)
Puddles such as peat water on the surface of the bending pavement can accelerate the aging process, disintegration and cause damage. The purpose of the study was to determine the effect of the aging process due to peat water soaking on the durability of the AC-WC mixture penetration 60/70 based on the Cantabro test. Research methods are laboratory tests that start from the design of asphalt concrete mixtures, determining KAO, LTOA tests, peat water chemical element tests. Soak asphalt concrete with peat water for 0, 1, 2, 4, and 7 days, CL Test and Marshall test. 7-day duration CL value 23.6%, stability 1805 kg, IDP 37%, IDK 34%. The chemical reaction element that causes LTOA is the oxidation reaction of asphaltenes due to the increase of the element oxygen that removes nitrogen (N) and alkyl chains (R). The chemical reaction element that causes aging due to peat water, namely organic substances affect the pH value depending on the number of lignin compounds. Lignin produces H ions that can accelerate aging. The pH value of peat water is 3, Na 78.81 mg/l, Fe 0.47 mg/l, organic substances 148.52 mg/l.